Pleione arunachalensis (Orchidaceae: Epidendroideae: Arethuseae: Coelogyninae), a new species from North-East India - Hareesh, Vadakkoot Sankaran; Kumar, Pankaj; Sabu, Mamiyil (Phytotaxa, 2017)
Pleione arunachalensis, a new species is described from Lower Dibang Valley district of Arunachal Pradesh, North-East India. Detailed descriptions, distribution, ecology, colour photographs and key to identification for Indian Pleione is provided.